2001
DOI: 10.1103/physrevlett.86.2317
|View full text |Cite
|
Sign up to set email alerts
|

MeV X Rays and Photoneutrons from Femtosecond Laser-Produced Plasmas

Abstract: We demonstrate a novel method to monitor the total angular distribution of the spectrum of hard x-ray emission from a plasma generated with femtosecond laser pulses with an intensity of 5 x 10(18) W/cm2 on a solid target. Measured and calculated angular distributions of x rays show a pronounced anisotropy for MeV photon energies. We complemented the spectral information by demonstrating a (gamma,n) nuclear reaction with a tabletop laser system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 179 publications
(94 citation statements)
references
References 34 publications
2
91
0
1
Order By: Relevance
“…at BD9, formed five bubbles during the laser shots. Schwoerer et al [16] have also demonstrated ( , n) reaction using 250 mJ laser pulses with pulse duration 60 fs.…”
Section: Epj Web Of Conferencesmentioning
confidence: 99%
“…at BD9, formed five bubbles during the laser shots. Schwoerer et al [16] have also demonstrated ( , n) reaction using 250 mJ laser pulses with pulse duration 60 fs.…”
Section: Epj Web Of Conferencesmentioning
confidence: 99%
“…The hot electron distribution was inferred by using parametrized one-and two-temperature test distributions to fit the measured channel responses. 20,21 Here we have used a genetic algorithm to determine the electron distribution underlying the measured response in the detector channels as produced by the emitted bremsstrahlung spectrum. The electron spectrum is sampled by a set of 17 discrete electron energies E j ranging from 20 keV to 10 MeV.…”
Section: A Hot Electron Spectramentioning
confidence: 99%
“…[1,2]. Emission of gamma-photons from a Ta target exposed in vacuum to peak intensity of 10 18 W/cm 2 in a femtosecond range of pulse duration results has been reported recently [3]. The average energy of these photons is about few MeV.…”
Section: Introductionmentioning
confidence: 99%